PELATIHAN MEDIA INTERAKTIF GOOGLE EARTH BAGI GURU SD INPRES SKP F3 ARSO - Ali, Aisyah; Hidayah, Hidayah; Marsuki, Marsuki; Korwa, Lofsten Festus (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This Training on the Use of Google Earth Media aims to enhance teachers' skills and understanding in using interactive media as an effective learning tool. The training focuses on introducing Google Earth features, accessing relevant content, and implementing technology-based learning strategies. The training method used is Participatory Rural Appraisal (PRA), which consists of preparation, implementation, and reflection stages. This activity was carried out at Inpres SKP F3 Arso Elementary School, Keerom Regency, with participants including the principal, classroom teachers, and subject teachers, totaling 13 people, on June 27, 2024. The training results showed an improvement in teachers' ability to use Google Earth; however, several limitations were identified, such as the lack of supporting devices and teachers' full understanding of this technology. The training had a positive impact on learning, but follow-up is needed by forming discussion groups for mentoring sessions to ensure the sustainability of interactive media use in the school environment